Development of Combined Load Spectra for Offshore Structures Subjected to Wind, Wave, and Ice Loading - Braun, Moritz (author); Dörner, Alfons (author); ter Veer, Kane F. (author); Willems, Tom (author); Seidel, Marc (author); Hendrikse, H. (author); Høyland, Knut V. (author); Fischer, Claas (author); Ehlers, Sören (author) (Energies, 2022)
Fixed offshore wind turbines continue to be developed for high latitude areas where not only wind and wave loads need to be considered but also moving sea ice. Current rules and regulations for the design of fixed offshore structures in ice-covered waters do not adequately consider the effects of ice loading and its stochastic nature on the fatigue life of the structure. Ice crushing on such structures results in ice-induced vibrations, which can be represented by loading the structure using a variable-amplitude loading (VAL) sequence. Typical offshore load spectra are developed for wave and wind loading. Thus, a combined VAL spectrum is developed for wind, wave, and ice action. To this goal, numerical models are used to simulate the dynamic ice-, wind-, and wave-structure interaction. The stress time-history at an exemplarily selected critical point in an offshore wind energy monopile support structure is extracted from the model and translated into a VAL sequence, which can then be used as a loading sequence for the fatigue assessment or fatigue testing of welded joints of offshore wind turbine support structures. This study presents the approach to determine combined load spectra and standardized time series for wind, wave, and ice action. Offshore Engineering